Total financial investment in maternal health care in Beijing and Shanghai: a comparison analysis - Dong-ping MA; Wen-qiang YIN; Zhuang TIAN (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo analyze the extent of deficit in total financial investment in maternal health care (MHC), the changing trend of maternal mortality rate (MMR) and their regional disparities in Beijing and Shanghai municipality during the period from 2000 through 2017 and to explore suitable total financial investment in MHC. Methods We searched China National Knowledge Infrastructure (CNKI) and Web of Science for research literatures on financial investment in MHC in Beijing and Shanghai municipality published during 1995 - 2017. The information on deficit in total financial investment in MHC was extracted from 205 retrieved studies for calculation of a severity score to evaluate the deficit in total financial investment in MHC. Spearman correlation and linear regression analysis were used to analyze the relationship between the deficit in total financial investment in MHC and MMR. Results For Beijing municipality, the severity score for the deficit in total financial investment in MHC decreased from 3.54 in 2000 to 2.78 in 2017, while for Shanghai municipality, the score decreased from 3.94 to 1.41. Regression analysis on the correlation between the deficit severity score and MMR resulted in statistically significant regression equations for both Beijing (P < 0.05) and Shanghai (P < 0.01). Conclusion The total financial investment in maternal health care increased gradually over the years in both Beijing and Shanghai municipality during 2000 - 2017. The influence of total financial investment on maternal mortality rate is more obvious for Shanghai. The study verified the feasibility of quantitative assessment on total financial investment in maternal health care.